P.002 Successful Treatment of Supra-Refractory Status Epilepticus Secondary to Anti-N-Methyl-D- Aspartate Receptor Encephalitis With Electroconvulsive Therapy. (November 2021) - AlSabah, A; Alshukaili, A; Teitelbaum, JS
Abstract : Background: Anti-N-Methyl-D-Aspartate (NMDA) receptor encephalitis is an autoimmune disease associated with antibodies against heteromers NR1 and NR2 subunits of the cell surface of the NMDA receptors, causing many psychiatric and neurological symptoms. This includes new-onset refractory status epilepticus. Methods: A 33-year-old previously healthy female developed new-onset refractory status epilepticus caused by anti- NMDA receptor encephalitis without the presence of tumours. Results: The clinical course was complicated by prolonged status epilepticus, which was refractory to many antiepileptic drugs (levetiracetam, phenytoin, carbamazepine, topiramate, lacosamide, valproic acid), ketamine, propofol, midazolam, including inhalation agents (isoflurane). Also, she received first (intravenous immunoglobulin, intravenous methylprednisolone, and plasmapheresis), second-line immunotherapy (rituximab) and prophylaxis bilateral oophorectomy without clinical or electrographic improvement. However, the patient drug-resistant status epilepticus markedly improved both clinically and electrographically following seven sessions of electroconvulsive therapy. Conclusions: Electroconvulsive therapy should be considered as adjuvant therapy for the treatment of immunotherapy resistant encephalitis.